Light diffuseness metric, Part 2: Describing, measuring and visualising the light flow and diffuseness in three-dimensional spaces. (June 2017) - Xia, L; Pont, SC; Heynderickx, I
We introduce a way to simultaneously measure the light density, light vector and diffuseness of the light field using a cubic illumination meter based on the spherical harmonics representation of the light field. This approach was applied to six light probe images of natural scenes and four real scenes built in our laboratory, and the results were compared to those obtained using Cuttle's method. We also demonstrated a way to simultaneously and intuitively visualise the global structure of the light distribution using light tubes and colour coding for the light density, light flow and diffuseness variations through the space. Together with Mury's work, we have a complete way to describe, measure and visualise the local and global low-order properties of light distributions in three-dimensional spaces.